Student Empowerment Training Through Socialization Of The Belanegara Program In Realizing Inter-Religious Harmony In Jember Regency - Thamrin, Mohammad (Universitas Muhammadiyah Jember, 2024)
This article discusses the concept of defending the country as the main foundation in ensuring the survival of the Indonesian nation and state. Defending the country is not only an obligation, but also a right of every Indonesian citizen as regulated in Law No. 3 of 2002 concerning State Defense. Efforts to defend the country include various forms of positive contributions, both in physical and non-physical actions, made by citizens in their daily lives. In the context of globalization, the spirit of defending the country has become increasingly relevant to face various threats to the existence and sovereignty of the nation. The role of educational institutions, including Islamic boarding schools, is very significant in instilling the values of love for the homeland, national awareness, and willingness to sacrifice. In addition, religious harmony and dialogue between religious communities are needed to strengthen national solidarity. This article also emphasizes the importance of understanding and anticipating various threats, both from within and outside the country, as well as the active participation of citizens in national defense efforts through education, training, and social activities. With the spirit of defending the country manifested in concrete actions, it is hoped that the Republic of Indonesia can remain upright and be able to face all challenges in the future